Pentingya Peran Serta Masyarakat Dalam Perlindungan Lingkungan, Perspektif Hukum Lingkungan - Mirary Chrisnalda Putra Ririassa; Jusuf Leiwakabessy; J.A.Y.Wattimena (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Community participation in environmental protection is a very important and main component so that the living environment where humans live is safe, comfortable and provides prosperity for humans. Ambon City is the capital of Maluku Province. Ambon City consists of several sub-districts. It can be seen that in recent years the Ambon city forest environment and residential areas have experienced several fires which resulted in destruction and damage to the environment along with buildings and structures as well as loss of life. This is what happened in South Leitimu District, Sirimau District, Nunaniwe District. The cause is indicated by the low level of community participation in protecting the environment. This can be seen from human negligence or negligence, deliberate human actions, human carelessness. The aim of this community service activity is to increase public knowledge and understanding through educational and socialization facilities in order to reduce to a minimum the damage and destruction of the environment along with the loss of life.